Information model of the automated control system by coolers on the thermal power stations and on the atomic power stations - Бердник, О. М. (Problems of Informatization and Control, 2008)
<span style="font-size: 13.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The structure of information model of the automated control system by coolers on the thermal power<span style="font-size: 13.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: Calibri; mso-ansi-language: UK; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> <span style="font-size: 13.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">stations and on the atomic power stations is presented. The model will allow to optimise functioning of<span style="font-size: 13.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: Calibri; mso-ansi-language: UK; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> <span style="font-size: 13.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">the chillers to regulate a situation with provision for weather conditions